Callanetics fit forever : an age-fighting, gravity-defying programme to look great and be strong, vital, and healthy for a lifetime /: an age-fighting, gravity-defying programme to look great and be strong, vital, and healthy for a lifetime. (2015) - Pinckney, Callan
No abstract available